Socially Response-able Mathematics Education: Implications of an Ethical Approach - Atweh, Bill; Brady, Kate (Eurasia Publishing House, 2009)
This paper discusses an approach to mathematics education based on the concept of ethical responsibility. It argues that an ethical approach to mathematics teaching lays the theoretical foundations for social justice concerns in the discipline. The paper develops a particular understanding of ethical responsibility based on the writings of Emanuel Levinas and discusses its implication for decision making on the curriculum and pedagogy in mathematics education. The paper argues that such an approach is consistent with a critical mathematics approach; however, it highlights the need to balance the concern about equity with that of quality. The paper concludes that this ethical stance, rather than being a normative criteria which dictates a particular line of action in different situations, it establishes a means to reflect on action and policy towards the achievement of more equitable access to high quality mathematics education.